Association of Chondrocalcinosis in Knee Joints With Pain and Synovitis: Data From the Osteoarthritis Initiative. Issue 11 (21st September 2017) - Han, Bobby Kwanghoon; Kim, Woojin; Niu, Jingbo; Basnyat, Shristi; Barshay, Veniamin; Gaughan, John P.; Williams, Charlene; Kolasinski, Sharon L.; Felson, David T.
Abstract : Objective: To evaluate the relationship between chondrocalcinosis and pain or synovitis in knee joints by examining data from the Osteoarthritis Initiative (OAI). Methods: Data were obtained from the OAI public‐use data sets. The relationship between chondrocalcinosis on baseline knee radiograph and pain at baseline and at 4 years was examined. Analyses were adjusted for age, sex, body mass index, and Kellgren‐Lawrence (K/L) grade and the correlation between 2 knees in a subject was controlled using generalized estimating equations. The relationship between chondrocalcinosis and synovitis on magnetic resonance imaging (MRI) was examined by comparing knees with chondrocalcinosis at baseline and age, sex, and K/L grade–matched knees with no chondrocalcinosis. We read MRIs of a subset of knees for synovitis using the MRI Osteoarthritis Knee Score (MOAKS) on baseline and 4‐year MRI. Results: Knees with chondrocalcinosis (n = 162) more often had pain compared to knees without chondrocalcinosis (n = 2, 030) at baseline and had higher Western Ontario and McMaster Universities Osteoarthritis Index pain scores, both at baseline (mean 2.4 [95% confidence interval (95% CI) 1.9, 2.9]) versus mean 1.8 [95% CI 1.7, 1.9]) and at 4 years (mean 2.5 [95% CI 1.9, 3.1] versus mean 1.6 [95% CI 1.5, 1.8]), as well as higher Intermittent and Constant Osteoarthritis Pain intermittent pain scores at 4 years. There was no difference in MOAKS synovitis scores at baseline and at 4 years between the chondrocalcinosis group (n = 102) and the control group (n = 99). Conclusion: Knees with chondrocalcinosis had increased pain and did not have higher synovitis scores on MRI compared to knees without chondrocalcinosis. The mechanisms by which chondrocalcinosis is associated with increased pain remain to be determined.